Potential production of struvite from the anaerobic digestion of food waste: analysis in one-phase and two-phase configurations - Brayan Alexis Parra-Orobio; Andrea Pérez-Vidal; Patricia Torres-Lozada (Water Science and Technology, 2021)
Anaerobic digestion (AD) of food waste (FW) has been gaining more interest as it has potential for the production of organic amendments with high struvite (NH4MgPO4·6H2O) content, which is a nutrient of great interest in sustainable agriculture. In this study, the influence of AD of FW in one- and two-phase configurations on methane production and the potential for struvite formation using digestate was evaluated. It was found that the two-phase is more efficient as its organic loading rate is 18% higher than that of one-phase configuration. In addition, the two-phase yielded a higher methane content in biogas (>60%) and a higher organic matter transformation in each of the AD stages (>20%); further, the digestate complied with the regulatory requirements for the use of organic amendments, thereby being deemed as a Type-B material with a struvite precipitation potential, exceeding 80%, as opposed to the digestate from one-phase configuration, which may represent a revenue of up to US$ 26,505 per year. HIGHLIGHTS Two-phase anaerobic digestion of food waste (AD-FW) is an alternative for the generation of struvite.; The presence of struvite helps the sanitization of the digestate obtained in the AD-FW.; Two-phase AD has potential for the treatment as well as energy and agricultural use of FW in small communities.;